Personalized Cancer Risk Assessments for Space Radiation Exposures - Locke, Paul A.; Weil, Michael M. (Frontiers in Oncology, 2016)
Individuals differ in their susceptibility to radiogenic cancers and there is evidence that this inter-individual susceptibility extends to HZE ion-induced carcinogenesis. Three components of individual risk: sex, age at exposure and prior tobacco use, are already incorporated into the NASA cancer risk model used to determine safe days in space for US astronauts. Here we examine other risk factors that could potentially be included in risk calculations. These include personal and family medical history, the presence of pre-malignant cells that could undergo malignant transformation as a consequence of radiation exposure, the results from phenotypic assays of radiosensitivity, heritable genetic polymorphisms associated with radiosensitivity, and post-flight monitoring. Inclusion of these additional risk or risk reduction factors has the potential to personalize risk estimates for individual astronauts and could influence the determination of safe days in space. We consider how this type of assessment could be used and explore how the provisions of the federal Genetic Information Nondiscrimination Act could impact the collection, dissemination and use of this information by NASA.